Alcohol Dehydrogenase 1B Suppresses β-Amyloid-Induced Neuron Apoptosis - Wang, Yaqi; Zhang, Yi; Zhang, Xiaomin; Yang, Tingting; Liu, Chengeng; Wang, Peichang (Frontiers in Aging Neuroscience, 2019)
Amyloid-β (Aβ) deposition, neurofibrillary tangles induced by phosphorylation of tau protein and neuronal apoptosis are pathological hallmarks of Alzheimer’s disease (AD).The dementia rate in the alcoholic abusers were found to be higher than the control people. The present study explored potential roles of alcohol dehydrogenase 1B (ADH1B) in AD pathological process.The results showed that ADH1B level decreased significantly both in the serum of AD patients and in the hippocampus of APP/PS-1 AD model mice.The apoptotic rate was reduced and the viability was elevated significantly for the AD model cell transfected with ADH1B over-expressed vector. Moreover,the level of p75 neurotrophin receptor (p75NTR), a receptor of Aβ1-42,was down-regulated in the ADH1B over-expressed AD model cell and up-regulated in the cells transfected with shRNA vector of ADH1B. Furthermore, the protein levels of cleaved caspase-3 and Bax decreased significantly, and Bcl-2 level increased in the cells when overexpressing ADH1B.The opposite trend of cleaved caspase-3,Bax and Bcl-2 were observed in the cells transfected with shRNA vector of ADH1B. The level of reactive oxidative species (ROS) was found to be reduced in the ADH1B over-expressed cells and be enhanced when transfected with shRNA vector of ADH1B. These results indicated that ADH1B might be significant in the prevention of AD, especially for the abusers of alcohol, and a new potential target of AD treatment.